A rapid method for isolation of stable niaD and crnA mutants of entomopathogenic fungi Beauveria bassiana and Metarhizium anisopliae - S. S. Sandhu; G. Venkateswerlu (Fungal Genetics Reports, 1997)
Generally niaD mutants of fungi are selected by spontaneous mutations on appropriate minimal medium supplemented with various concentrations of KClO3 and a nitrogen source (Daboussi et al. 1989 Curr. Genet. 15:453-456; Johnstone et al. 1990 Gene 90:181-192; Malardier et al.1989 Gene 78:147-156; Unkles et al.1989 Gene 78:157-166). But in case of entomopathogenic fungi it has been observed that niaDmutants isolated simply by spontaneous mutation on chlorate were not stable, (Table-1). Therefore a method has been developed to isolate stable niaD mutants of these fungi by treating protoplasts with ethane methane sulfonate (EMS).